Hematology and biochemistry reference intervals in chemically immobilized free-ranging giant anteaters (Myrmecophaga tridactyla) - Alves, Mario H.; Kluyber, Danilo; Alves, Amanda C.; Yogui, Débora R.; Pereira, Fernanda M. A. M. [UNESP]; Costa, Miriã R.; Attias, Nina; da Silva, Polyana Mayume Pereira; Desbiez, Arnaud L. J. (Springer Nature, 2023)
The giant anteater (Myrmecophaga tridactyla) is classified as a vulnerable species but is commonly received in rescue centers and zoos. Establishing hematological and biochemical reference intervals of free-ranging animals is an important tool to assess the health of both captive and wild populations. Reference values for 53 free-ranging giant anteaters in the Cerrado savanna of Mato Grosso do Sul state were established and differences across sexes and age groups were tested. Significant differences (p ≤ 0.05) between age groups (juvenile and adult) were found for hematocrit, mean corpuscular hemoglobin concentration (MCHC), lymphocytes, monocytes, platelets, total protein, globulin, alkaline phosphatase (ALP), glutamyl transpeptidase (GGT), and phosphorus. Between sexes, the only value that showed a significant difference was platelets. The data from the present study were also compared with previous studies and a worldwide zoological databank (ZIMS). White blood cell values were higher in all the studies with free-ranging giant anteaters compared to captive individuals. The relative eosinophils reference interval from our study was the highest ever reported for the species. This paper is the first published study with biochemical values for free-ranging giant anteaters and provides important reference intervals for future giant anteater in situ and ex situ conservation initiatives and highlights the importance of more veterinary research with comparative aspects between wild and captive animals.
Keywords: Age-related effect; Health assessment; Pilosa; Wildlife; Xenarthra